2004
DOI: 10.5483/bmbrep.2004.37.5.612
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Expression Profile of Cyst Epithelial Cells in Autosomal Dominant Polycystic Kidney Disease Patients

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a common genetic disorder characterized by the formation of fluid-filled cysts in the kidney and progressive renal failure. Other manifestations of ADPKD include the formation of cysts in other organs (liver, pancreas, and spleen), hypertension, cardiac defects, and cerebral aneurysms. The loss of function of the polycystin -1 and -2 results in the formation of epithelium-lined cysts, a process that depends on initial epithelial proliferation. cDNA microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Comparing our results with those of the transcriptomal analysis of ADPKD patients reported by Schieren et al (49), only 23 of the 85 genes that they selected demonstrated a regulation pattern similar to those of the genes analyzed in our study. In the case of the transcriptomal analysis of cultured cells derived from ADPKD patients by Lee et al (50), as few as 7 of the 52 genes selected showed a regulation pattern similar to that of the genes analyzed by us; moreover, 12 genes demonstrated opposite regulation. In addition, Mmp12 that was observed to be greatly up‐regulated (23.87‐fold) in the kidneys of Aqp11 –/– mice in our study (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Comparing our results with those of the transcriptomal analysis of ADPKD patients reported by Schieren et al (49), only 23 of the 85 genes that they selected demonstrated a regulation pattern similar to those of the genes analyzed in our study. In the case of the transcriptomal analysis of cultured cells derived from ADPKD patients by Lee et al (50), as few as 7 of the 52 genes selected showed a regulation pattern similar to that of the genes analyzed by us; moreover, 12 genes demonstrated opposite regulation. In addition, Mmp12 that was observed to be greatly up‐regulated (23.87‐fold) in the kidneys of Aqp11 –/– mice in our study (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Kidney samples for lectin staining were frozen in liquid nitrogen into Tissue Tek OCT compound (Miles; Elkhart, IN, USA) and stored at −70 °C until sectioned. Sections Table 2 Comparison of renal mRNA expression among inv∆C mice in the present study, pcy mice (Nakamura et al 1993;Gattone et al 1996), human ADPKD cells (Husson et al 2004;Lee et al 2004) and cpk mice (Gattone et al 2002) were performed at 10 µm, and fixed in 4% PFA in 0.1 m phosphate buffer, pH 7.5 at room temperature for 20 min. FITC conjugated LTA and rhodamine conjugated DBA were used at a concentration of 50-100 µg/mL in PBS.…”
Section: Histological Analysis and Lectin Stainingmentioning
confidence: 92%
“…1 In ADPKD, arachnoid cysts have been reported to co-exist. 2 The observations of familial occurrence of arachnoid cysts, 2,3 in combination with the observed co-existence of arachnoid cysts and genetically determined cystic diseases, 2,3 indicate a genetic component in the cystogenesis of at least some of the arachnoid cysts.…”
mentioning
confidence: 99%